Efficacy of application of new laser technologies at multistage method of surgical treatment of patients with high posttraumatic fistulas of rectum - M. M. Mamedov; N. I. Mamedov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study potential of application of up-to-date laser technique and new technologies at multistage method of surgical treatment of patients with high posttraumatic fistulas of rectum.Material and methods. At 46 patients with posttraumatic fistulas of rectum the multistage method of surgical treatment with application of modern laser technique, specific instruments and new technologies was utilized. During operation (at resection of intestine, resection of necrotic tissues and stumps of fistulous tract, management of purulent sinus) carbon dioxide laser device «Lancete-2» (wave length – 10,6 microns) and contact laser device «Atkus-15» (wave length – 0,81 microns) were used. The surgical intervention in 2 stages has been executed at 11 (23,9%), in 3 stages – at 31 (67,4%) and in 4 stages – at 4 (8,7%) patients.Results. The multistage method of surgical treatment with application of modern laser technique and new technologies allows to stop inflammatory process in pararectal fat, provides an option of combined surgical interventions, improves functional results, decreases of frequency of relapses, shortens terms of wound repair and decreases the risk of development of incompetence of anal sphincter.Conclusions. At localization of internal fistulous orifice in lower-, middle- and highampullary parts of rectum with severe inflammatory complications and purulent sinuses on within fistula tract, concomitant anal incontinence multistage surgical treatment is required. Application of original procedure allows to achieve high-grade medical and social rehabilitation of patients.